Examining the Role of Local Media in Political Communication during the 2024 Simultaneous Regional Elections: A Case Study in Bima City - Tasrif; Haeril (KOMUNITAS, 2024)
This research investigates the role of local media in political communication during the 2024 Simultaneous Regional Elections in Bima City, focusing on how accessible information affects candidate electability. It highlights challenges faced by local media, including political bias that undermines reporting objectivity and how shifts in political party support alter public perceptions. The study aims to assess how local media presents political information and its impact on public participation, as well as how local media adapt to the digital age through social media engagement by politicians. Findings indicate that local media significantly enhance political education and public involvement, although issues regarding independence and neutrality persist. While local media effectively disseminate information about candidates and their programs, biases can sway public opinion and impact democratic quality. The research concludes that improving professionalism and commitment to balanced journalism principles is essential for fostering a more transparent and accountable democratic process.